2019
DOI: 10.3390/rs11192303
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Channel Weather Radar Echo Extrapolation with Convolutional Recurrent Neural Networks

Abstract: This article presents an investigation into the problem of 3D radar echo extrapolationin precipitation nowcasting, using recent AI advances, together with a viewpoint from ComputerVision. While Deep Learning methods, especially convolutional recurrent neural networks, havebeen developed to perform extrapolation, most works use 2D radar images rather than 3D images.In addition, the very few ones which try 3D data do not show a clear picture of results. Throughthis study, we found a potential problem in the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The spatial memory can preserve the spatial information from the bottom to the top layer. Also, Tran., et al [17] showed that it can be applied in radar echo extrapolation and deliver better performance than ConvLSTM. However, the extra spatial memory does not help the input or the hidden state to select important features because they are convolved independently.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial memory can preserve the spatial information from the bottom to the top layer. Also, Tran., et al [17] showed that it can be applied in radar echo extrapolation and deliver better performance than ConvLSTM. However, the extra spatial memory does not help the input or the hidden state to select important features because they are convolved independently.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the number of successful cases of application of deep learning in real life, such as in autonomous driving, healthcare, and smart cities [1][2][3][4][5][6][7][8][9], various attempts have been made to apply deep learning to weather-related fields using numerical models [10] to improve the performance of weather forecasting [11][12][13][14][15]. In the field of meteorology, nowcasting is a popular research topic in which deep learning techniques are being actively applied to the analysis of spatiotemporal data, such as radar and satellite data [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen et al [49] proposed a satellite imagery-based CNN for estimating the tropical cyclone intensity. Tran and Song [50] predicted multichannel radar image sequences by using deep neural network-based image processing techniques. Lee et al [51] adopted CNNs using image patterns to estimate the tropical cyclone intensity by mimicking human cloud pattern recognition.…”
Section: Introductionmentioning
confidence: 99%